The Aesthetics of Sundanese Traditional Design, Case study: Rice Containers Design - Jamaludin Jamaludin (Journal of Visual Art and Design, 2013)
The traditional design that is still made and exists today is a legacy from mythical culture period. That is to say that it has its own aesthetical concept that is different from modern aesthetics. Some of the traditional designs in Sundanese society is the rice containers that come in different form depends on the rice condition. The design of a traditional rice container in Sundanese culture is made in basic shapes, such as square, circle and triangle or configuration of the basic shapes resulted in a beautiful design. The rice containers mostly made of woven bamboo. Uniquely, these visual basic shapes also found in proverbs and idioms in Sundanese language as a symbol of perfection of conduct.  Square symbolizes attitude or behavior, circle is for belief or faith, and triangle represents a holy place. Rice in traditional community such as Baduy in Banten has a connection with the myth of the goddess of rice. Thus, Sundanese traditional culture and society highly respect the rice. This is one of the reasons why the traditional rice containers are designed in those form. This study has come to a conclusion that traditional design made is not merely to fulfill utility needs but also to represent the Sundanese macrocosm.